The tracking and tracing technology integration in supporting Smart City Concept / N. M. Nor ... [et al.] - N. M., Nor; N. A., Wahap; N., Ahmad; N. M., Yusoff; N.A. M, Ismail (2014)
The world is undergoing the largest wave of urban growth in history. As reported by the Department of Economic and Social Affairs United Nation, 54% of the world’s population lives in urban areas and this proportion is expected to increase to 66% by year 2050. To handle the large scale of this population’s waved; the city or urban area should by now have completely has a sustainable infrastructure component and a strong technology support to serve the citizen. To counter this problem, smart city concept has been proposed. Smart city can be defined as a developed urban area that aims to increase citizen’s quality of life by creating sustainable economic development, through technology utilization, integration and enhancement. Tracing and tracking is one of the components that support smart city concept. It combines the related technologies to perform the smart city application such as the mobile workforce. The objective of this study was to understand the concept of tracing and tracking in supporting the smart city. An example of smart city application which is the mobile workforce has been taken out for testing purposes. During testing, related technologies are then being identified and listed its technical potential. Finally, the technology integration is reviewed and compared to ensure its performance contribute to a new way of living.